Cross-border mergers and acquisitions: a bibliometric review and future research avenues - Reis, Nuno (2019)
Cross-border mergers and acquisitions (CBMAs) are an important mode of international expansion and have attracted substantial scholarly attention in the last decades. The extant literature on CBMAs is fragmented and often presents contradictory perspectives which hinder the researchers’ ability to understand the phenomenon. Therefore it is useful to analyse the extant literature on CBMAs, to make sense of what has been published, in a systematic and objective way. In this paper we conduct a bibliometric review of CBMA research over a 20-year period (1994–2013). Using a sample of 256 articles published in 69 journals we performed citation, co-citation and factor analyses, structural and longitudinal, to understand the most influential works and to observe the evolution of the themes and theoretical approaches used. We identified the importance of culture-related works as well as the increasing importance of resource-and knowledge-related approaches, whereas finance/economics perspectives have a decreasing influence.